Epilepsy surgery outcomes in patients with GATOR1 gene complex variants: Report of new cases and review of literature. (April 2023) - Sahly, Ahmed N; Whitney, Robyn; Costain, Gregory; Chau, Vann; Otsubo, Hiroshi; Ochi, Ayako; Donner, Elizabeth J; Cunningham, Jessie; Jones, Kevin C; Widjaja, Elysa; Ibrahim, George M; Jain, Puneet
Highlights: Pathogenic GATOR1 variants - important etiology of medically refractory epilepsy in children. GATOR1-related disease spectrum wide – includes focal seizures, epileptic spasms and neurodevelopmental delay. Epilepsy surgery remains an important treatment consideration for focal epilepsy secondary to GATOR1 variants. Favourable surgical outcomes in GATOR1-related focal epilepsy seen in 50–60% cases. Abstract: Aim: To report seizure outcomes in children with GATOR1 gene complex disorders who underwent epilepsy surgery and perform a systematic literature search to study the available evidence. Methods: The records of children with pathogenic/likely pathogenic variants in GATOR1 gene complex who underwent epilepsy surgery were reviewed. Clinical, radiological, neurophysiological, and histological data were extracted/summarized. The systematic review included all case series/reports and observational studies reporting on children or adults with genetic (germline or somatic) variants in the GATOR1 complex genes ( DEPDC5, NPRL2, NPRL3 ) with focal epilepsy with/without focal cortical dysplasia who underwent epilepsy surgery; seizure outcomes were analyzed. Results: Eight children with pathogenic/likely pathogenic variants in GATOR1 complex genes were included. All had drug-resistant epilepsy. Six children had significant neurodevelopmental delay. Epilepsy surgery was performed in all; clinical seizure freedom was noted in 4 children (50%). Systematic literature search identified 17 eligible articles; additional 30 cases with patient-level data were studied. Lesional MRI brain was seen in 80% cases. The pooled rate of seizure freedom following surgery was 60%; FCD IIa was the most encountered pathology. Interpretation: Epilepsy surgery may be effective in some children with GATOR1 complex gene variants. Seizure outcomes may be compromised by extensive epileptogenic zones.